Performance of Passive Samplers for Monitoring Estuarine Water Column Concentrations 1. Contaminants of Concern - Perron, Monique M. (2013)
Contaminants enter marine and estuarine environments and pose a risk to human and ecological health. Recently, passive sampling devices have been utilized to estimate dissolved concentrations of COCs, such as polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs). In the present study, the performance of three common passive samplers was evaluated for sampling PAHs and PCBs at several stations in the temperate estuary Narragansett Bay (Rhode Island, USA). Sampler polymers included polyethylene (PE), polydimethylsiloxane (PDMS) coated solid phase microextraction (SPME) fibers, and polyoxymethylene (POM). Dissolved concentrations of each contaminant were calculated using measured sampler concentrations adjusted for equilibrium conditions with performance reference compounds (PRCs) and chemical-specific partition coefficients derived in the laboratory. Despite differences in PE and POM sampler concentrations, calculated total dissolved concentrations ranged from 14–93 ng/L and 13–465 pg/L for PAHs and PCBs, respectively. Dissolved concentrations of PAHs were approximately three times greater based on POM compared to PE while dissolved concentrations of PCBs based on PE were approximately three times greater than POM. Concentrations in SPME were not reported due to the lack of detectable chemical in the amount of PDMS polymer deployed. Continued research is needed to improve and support PE and POM use for the routine monitoring of COCs. For example, a better understanding of the use of PRCs with POM is critically needed.